Sun’s procedure of total arch replacement using a tetrafurcated graft with stented elephant trunk implantation: analysis of early outcome in 398 patients with acute type A aortic dissection - Ma, Wei-Guo; Zheng, Jun; Dong, Song-Bo; Lu, Wei; Sun, Kai; Qi, Rui-Dong; Liu, Yong-Min; Zhu, Jun-Ming; Chang, Qian; Sun, Li-Zhong (Annals of Cardiothoracic Surgery; Vol 2, No 5 (September 01, 2013): Frozen Elephant Trunk, 2013)
Background: Acute type A aortic dissection (AAAD) remains one of the most lethal conditions requiring surgical repair, and is associated with a high rate of postoperative mortality and morbidity. Despite the satisfactory clinical outcomes achieved with the frozen elephant trunk technique so far, controversies still exist regarding the use of this aggressive approach in patients with AAAD. In this study, we seek to analyze the early outcomes of the Sun's procedure, which is an approach integrating total arch replacement using a 4-branched graft with implantation of a special stented graft in the descending aorta, and identify the risk factors for postoperative mortality and morbidity of the Sun’s procedure in patients with AAAD. Methods: Clinical data of 398 consecutive AAAD patients undergoing the Sun’s procedure were analyzed. The associations between 20 preoperative and intraoperative variables and early mortality were assessed by univariate and multivariate analysis. Results: Early mortality occurred in 31 patients (7.8%, 31/398), and the leading causes was multi-organ failure in 16 patients (51.6%), permanent neurologic deficit in 6 (19.4%), and low cardiac output syndrome in 4 (12.9%). Permanent neurologic deficit and spinal cord injury occurred, each in 10 patients (2.5%, 10/398). Five significant risk factors for early mortality were identified with multivariate analysis: preexisting cerebrovascular disease [relative risk (RR) 14.76; P